Effects of home-based breathing exercise on heart rate variability, cardio-ankle vascular index, respiratory muscle strength and maximum oxygen consumption in female participants with normal weight obesity - Inthachai, Tharnwimol; Demeekul, Kanokwan; Sawatmongkul, Chanya; Somboonchai, Sukrit; Pluksek, Artitaya; Tunpha, Benchawan (Journal of Associated Medical Sciences, 2020)
Background: Obesity causes autonomic imbalance and decreases exercise capacity, which limit exercise and physical activity. Normal-weight obesity (NWO) is defined as normal body mass index (BMI), but increased body fat percentage (BF%) associated with cardiorespiratory impairment in early adulthood. The benefit of slow breathing has shown to enhance cardiorespiratory functions in overweight and generally obese people. Moreover, the slow breathing affects to the heart rate variability (HRV), cardio ankle vascular index (CAVI), respiratory muscle strength and indirect maximum oxygen consumption (indirect VO2max) has not been studied in female individuals with NWO. Objectives: To determine the effects of slow breathing exercise on HRV, CAVI, respiratory muscle strength and VO2max in female participants aged 20-30 years, who have normal BMI (18.5-22.9 kg/m2, n=19 each group) and high body fat (BF) (BF ≥30%), compared with a control group, which carried out routine physical activity. Materials and methods: Participants with NWO were divided randomly into two groups: control and intervention group, which performed breathing exercise at home. All of the participants were measured for body composition, blood pressure, HRV and CAVI. An electronic pressure transducer and cycle ergometer were applied to assess respiratory muscle strength and indirect VO2max. All measurements were recorded before and after 4 weeks when completely intervention. The demographic data between the groups was analyzed the significant difference by using the independent t test. The data at baseline and four weeks after intervention was determine by two way ANOVA. P-value less than 0.05 was considered statistically significant. Results: Participants with NWO, who received breathing exercise at home, showed lower autonomic imbalance, and systolic blood pressure, whereas improved maximum inspiratory pressure (MIP), but no statistical change in maximum expiratory pressure (MEP), indirect VO2max, CAVI or ankle brachial index (ABI) (p>0.05). Conclusion: Slow breathing exercise can improve autonomic balance and inspiratory muscle strength in physically inactive female NWO participants.